Hubungan Asia Tenggara–Usmani dalam Arsip Turki - Burhanudin, Jajat (Studia Islamika, 2023)
Ismail Hakki Kadi and A.C.S. Peacock (eds.). 2022. Ottoman-Southeast Asia Relations, 2 vols. Leiden and Boston: BrillThe glorification of the Ottoman Empire, often legitimized by specific Muslim groups in Indonesia in the past two decades, has frequently steered toward myth-building rather than the advancement of knowledge through historical sources. This book represents an endeavour to present comprehensive data on the relationship between Southeast Asia and the Ottoman Empire through research centred on the theme of “Islam, Trade and Politics across the Indian Ocean” during the years 2009-2011, with a focus on the archives of the Turkish Presidential Archives in Istanbul. The book unveils crucial puzzles in the history of Islam in Southeast Asia concerning diplomatic relations with the Islamic superpower, encompassing the period from the early encounters with Western powers and continuing into the Colonial Era. In addition to examining primary sources of diplomatic relations between the kingdoms of Aceh, Kedah, Riau, Jambi, and Brunei with the Ottoman Empire, this book also reveals the political, economic, and socio-religious dynamics as they unfolded in Batavia, Singapore, and the Philippines.